Biophysico-chemical processes of anthropogenic organic compounds in environmental systems - Xing, Baoshan; Senesi, N. (Nicola); Huang, P. M. (Hoboken, N.J. : John Wiley & Sons, 2011)
In contrast to the classical books which largely focus on separate, individual physicochemical and biological aspects, this book aims to integrate the frontiers of knowledge on the fundamentals and the impact of physicochemical and biological interactions and processes of AOCs in soil, sediment, water and air.€ The specific objectives of this book are to address: (1) fundamental biophysico-chemical processes of AOCs in the environment, (2) occurrence and distribution of AOCs in air, water, and soil, and their global cycling, (3) the state-of-the-art analytical techniques of AOCs, and (4).
pt. 1. Funamental biophysico-chemical processes of anthropogenic organic compounds in the environment -- pt. 2. Anthropogenic organic compounds in air, water, and soil, and their global cycling -- pt. 3. Analytical techniques -- pt. 4. Restoration of natural environments contaminated by organic pollutants.
Print version record.
Keywords: Environmental chemistry; Bioorganic chemistry; Anthropogenic soils; Engineering; Environmental engineering; TECHNOLOGY & ENGINEERING -- Environmental -- Pollution Control; Anthropogenic soils; Bioorganic chemistry; Environmental chemistry; Electronic books